Development of rough grinding equipment for raw biomass resource - Muhammad Haikal, Abdullah (2013)
This researchdeals with the development of rough grinding equipment for raw biomass resource.Significant of this project is to provide equipment to grind the raw biomass materials and produce standard size of particle materials. The objective of this thesis is to develop grinding machine for raw biomass and to fabricate a grinding machine for raw biomass. The thesis describes finite element analysis techniques to predict the displacement magnitude and identify the worst stress locates in the structures. The structural of three-dimensional solid modeling of the machine grinding was developed using Solidworks software. The strategy of validation of finite element model was developed. The finite element analysis was then performed using SolidWorks Simulation. The machine grinding for biomass structure was analyzed using the static stress with linear material models approaches. The result of simulation show the minimum factor of safety is greater than 1 which means this frame and shaft machine grinding is in safe condition. In fabrication process,the machine grinding will be fabricated based on the design has been made. Fabrication process has involves mechanical processes such as grinding, drilling, cutting, milling and etc. Test run on the machine grinding will be done after all process had been completed to get the standard size of particles from output materials. As a conclusion, the development of rough grinding equipment for raw biomass resource was been developed and the result of the simulation and output materials from machine grinding show the positive result.